Moving out of poverty : (The World Bank, 2009)
Why and how do some people move out of poverty and stay out while others remain trapped? Most books on growth and poverty reduction are dominated by the perspectives of policy makers and academic experts. In contrast, Moving Out of Poverty: Success from the Bottom Up presents the experiences of poor people who have made it out of poverty.